ISSP 1996 - Role of government III: Sweden - Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 1996 'International Social Survey Program'. Citizens' opinions were elicited on the function of their national governments and on what governments should and should not be doing. Respondents were asked whether they approved of economic policies such as wage and price controls, job creation programs, including public work projects, support for ailing private industries, and the forced reduction in the industrial work week, as well as conservative measures, such as reductions in government spending and business regulations. Government spending was another topic, with respondents questioned as to their support for greater spending on the environment, health care, police and law enforcement, education, military and defence, culture and the arts, old age pensions, unemployment benefits, and housing for the poor. A number of questions dealt with respondents' attitudes regarding democracy, political power, and protest. Respondents were asked for their views on the rule of law when it is in conflict with private conscience, various forms of anti-government protest (public meetings, protest marches and demonstrations, nationwide strikes), whether the right to protest should be afforded to those who advocate the overthrow of the government by revolution, and the conflict between security needs and privacy rights. Other questions focused on the role of elections in democracies, including whether voters understand political issues, whether elections force governments to confront pressing political issues, whether certain institutions (unions, government, business and industry) have too much power in affecting election results, whether politicians really try to keep their election promises, whether civil servants can be trusted to work in the public´s interest, and whether various industries (power companies, hospitals, banks) are better off being run by the private sector or by the government. Opinions were also elicited as to whether government had a legitimate role in the redistribution of wealth in the country, by tax policy or otherwise. Demographic variables include age, sex, education, marital status, personal and family income, employment status, household size and composition, occupation, religion and church attendance, social class, union membership, political party, voting history, and ethnicity.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 1996 investigating The Role of Government.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 1996 är ”The Role of Government”. Detta är tredje gången studien genomförs på det här temat och har sedan genomförts ytterligare en gång på samma tema (SND 0849).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 1996 undersöker åsikter om politik och den offentliga sektorn.
ISSP 1996 - Åsikter om politik och den offentliga sektorn
Keywords: public sector; offentlig sektor; social welfare; social välfärd; taxation; beskattning; internal politics; inrikespolitik; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Sociology; Sociologi